TECHNICAL AND SCALE EFFICIENCY OF FOOD PRODUCERS IN POLAND IN2006-2016. DOES THE SIZE AND LEGAL STATUS OF ENTERPRISES MATTER ? - Sylwester Kozak (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The article empirically examines how the size and legal status of an enterprise influence thetechnical and scale efficiency of Polish food producers. Technical and scale efficiency indices are measuredusing the non-parametric DEA method. The study is based on the annual financial reports of 52 sugar andconfectionery producers operating in 2006-2016. The analysis covers all enterprises in the sector, as well asgroups of larger and smaller enterprises (distinguished by the median of assets), as well as groups of capitalcompanies and cooperatives. Research has shown that enterprises were characterized by relatively hightechnical efficiency and scale efficiency in the range, respectively, between 82 and 93% and between 93and 98%. All enterprises operated more efficiently in more favorable macroeconomic conditions. The levelof enterprises’ technical and scale efficiency depends on the value of their assets and the legal status. Largerenterprises were less technically effective than smaller ones, but they made greater use of the effect of scale.Capital companies were more effective than cooperatives, but to a lesser extent used economy of scale.